SUPUESTA LOCALIDAD TIPO DE COLIAS IMPERALIS BUTLER (LEPIDOPTERA: PIERIDAE) - Shapiro, Arthur M. (Acta Entomológica Chilena, 2022)
The true type-locality of Colias imperialis Butler and its sénior synonym C. ponteni Wall, remains unknown. Butler supposed it carne from Port Famine, based on the type-series being housed in the British Museum with material collected there by the Adventure expedition. Wallengrén gave the type-locality of C. ponteni as Honolulú, Hawaii, which is very improbable, but the Eugenie expedition had also stopped briefly at Port Famine and G. Lamas inferred that the types were probably collected by that ship’s naturalists on an expedition to Cerro Tam. However, neither the vegetation ñor the climatology, ñor the published narratives of both expeditions, supports these inferences. If this is truly a Magellanic insect it probably was taken in steppe habitat farther north, perhaps at the classical "Cabo Negro" locality or near Punta Delgada. The species is so important for phylogeny reconstruction that every effort should be made to rediscover it.